Perceived Development of Sustainable Agriculture - Maja Klun; Renata Slabe Erker (Central European Public Administration Review)
Within the concept of sustainable agriculture, the two fields of administration of the Ministry of Agriculture and the Environment come face to face, resulting in a number of social implications. In order to provide assistance in the shaping, execution and assessment of sustainable activities, in this article we analyse the attitude of the public and farmers towards sustainable development in agriculture. The results reveal that in Slovenia, sustainable agriculture has support not only on the level of declarations, but also among the public. Statistically significant differences between the general public and farmers can be noted in the groups’ respective understandings of the sustainable advancement of agriculture in the field of the environment. In parallel to this, a rift can be noted between support for sustainable agriculture in principle and in practice. For this reason, it would be wise to consider shifting the focus of agricultural policy measures from environmental sustainability to social sustainability and the survival of farmers, along with an emphasis on positive environmental information regarding Slovenian farmers.